2020
DOI: 10.1007/s40962-020-00428-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rotary Degassing Treatments on the Melt Quality of an Al–Si Casting Alloy

Abstract: In order to produce cast components, which meet the quality requirements of the automotive and aerospace industries, the control of liquid metal quality prior to the casting process is essential. Rotary degassing is the most commonly used melt treatment method in the foundry industry, which can effectively reduce the inclusion and solute hydrogen content of the metal. This procedure is often combined with fluxing, which allows more efficient inclusion removal during melt processing. In this study, the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…On the other hand, no significant improvement was achieved by degassing with N 2 . The number of bifilms present in the melt was even increased by the treatments with N 2 , which is in accordance with the findings of Gyarmati et al [39] and the LiMCA data reported by Tremblay and Maltais. [50] During the investigation of K-mold samples, in all cases, film-like discontinuities were found, which comprised of two distinct layers that could be clearly seen on the opposing fracture surfaces (Figure 9).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, no significant improvement was achieved by degassing with N 2 . The number of bifilms present in the melt was even increased by the treatments with N 2 , which is in accordance with the findings of Gyarmati et al [39] and the LiMCA data reported by Tremblay and Maltais. [50] During the investigation of K-mold samples, in all cases, film-like discontinuities were found, which comprised of two distinct layers that could be clearly seen on the opposing fracture surfaces (Figure 9).…”
Section: Resultssupporting
confidence: 92%
“…[32][33][34][35] According to Campbell, [3] degassing treatments are only effective in removing relatively large-sized bifilms, while numerous small-sized bifilms can be introduced into the liquid metal during the treatments. This statement is in accordance with the findings of Lazaro-Nebreda et al, [36] Yorulmaz et al, [37] Dispinar and Campbell, [38] as well as Gyarmati et al [39] As was highlighted by Cao and Campbell, [40] the purging gases, which are often considered inert, could contain trace oxygen and water vapor which can lead to the oxidation of the inner surface of the purging gas bubbles. N 2 readily reacts with liquid Al at temperatures above 700 °C and forms AlN, which reaction can even be utilized for manufacturing Al-AlN composites.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The decrease in the mechanical properties due to the presence of double oxide defects is well known [12][13][14], and it affects the components produced by gravity casting [15] and low-pressure casting [16,17]. An accurate preparation of the melt with degassing and filter systems is effective for preventing the entrainment of thick bifilms (thickness = 10 μm ÷ 1 mm) inside the casting [8,12,18]. In contrast, thinner bifilms, generated by the action of turbulence during the pouring and filling phases, are difficult to eliminate, due to their small size (thickness = 1 nm ÷ 1 μm) [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study [5] applies ultrasonic vibration with a combination of argon blowing. However, according to another sources [6][7][8] the most used degassing methods are rotor devices, which reduce the hydrogen content to the desired values within a few minutes. The principle of the machine consists in blowing an inert gas into the molten alloy bath.…”
Section: Introductionmentioning
confidence: 99%